How Internship Experience, Self-Efficacy, and Digital Literacy Shape Work Readiness Among Final-Year Students - Ira Setyawati; Oktafiano Reinaldi Angelo Magang (Bina Nusantara University, 2026)
This study explores the impact of self-efficacy, digital literacy and internship experience on the readiness of Indonesian final-year university students to enter the workforce. This study used the quantitative survey approach with 190 respondents from 28 provinces in Indonesia, driven by the ongoing discrepancy between graduate competencies and labor market needs. Data were collected with a five-point Likert scale and analyzed with multiple linear regression using IBM SPSS Statistics version 30. The results showed that work preparation was considerably increased by digital literacy, self-efficacy, and internship experience, which explained 53.4% of the variance. The most predictor is self-efficacy that psychological preparation has an important role in graduate employability. In stepwise analysis, the only skills that exhibited significant effects were career-related skills in digital literacy and trust competency in self-efficacy and explicit goals in internship experience, as the most contributing factors. The result support the Social Cognitive Career Theory paradigm and indicate the importance of an integrative approach, which includes career-oriented digital competence, psychological empowerment, and experiential learning for work readiness. Higher education institutions are recommended to improve training of digital skills in alignment with the industry, development of self-efficacy and structured internship programs to better prepare graduates for the current profession.